Comparison of Indonesian and Dutch Laws on the Implementation of Euthanasia - Fitri, Winda; Tan, Winsherly; Putri, Aulia Ginda (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
Developments in various matters cannot be separated from the regulations attached to them, one of which is related to euthanasia. Euthanasia in general is a treatment given to a patient to end his life intentionally with the aim of escaping suffering. Euthanasia is divided into two types, namely active euthanasia and passive euthanasia. Until now, the act of euthanasia still has pros and cons, including in Indonesia. However, there are also countries that have legalized this, such as the Netherlands. This article will raise issues related to the positive legal regulation of euthanasia in Indonesia and the Netherlands as countries that have legalized euthanasia in terms of human rights and the Criminal Code. The research method is normative juridical research with a comparative approach. The results show that legal regulations related to euthanasia in Indonesia have not yet been specifically regulated even though the act of euthanasia is absolutely prohibited. From a criminal law perspective, the act of euthanasia is subject to Article 338 and Article 344 of the Criminal Code, the implementation of which still creates uncertainty. For families who submit euthanasia, Article 345 of the Criminal Code applies. Meanwhile, the Netherlands has had a law relating to euthanasia since 2001 which is followed by procedures and conditions for its implementation based on Dutch Penal Code 293 and 294 of Dutch law. The formation of regulations related to euthanasia is necessary in Indonesia if it needs to be hastened considering the progress of the times and the mindset of humans who know information easily and can find out about euthanasia